2019
DOI: 10.1021/acs.jctc.8b01107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of All-Atom Molecular Mechanics Force Fields on Amyloid Peptide Assembly: The Case of Aβ16–22 Dimer

Abstract: We investigated the effects of 17 widely used atomistic molecular mechanics force fields (MMFFs) on the structures and kinetics of amyloid peptide assembly. To this end, we performed large-scale all-atom molecular dynamics simulations in explicit water on the dimer of the sevenresidue fragment of the Alzheimer's amyloid-β peptide, Aβ16−22, for a total time of 0.34 ms. We compared the effects of these MMFFs by analyzing various global reaction coordinates, secondary structure contents, the fibril population, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
161
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(166 citation statements)
references
References 87 publications
3
161
0
2
Order By: Relevance
“…Due to the complexity of the parameterization process, various force fields are not guaranteed to exhibit the same effect on biomolecular behavior. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] This has been seen previously when modifica-tions to torsion angle parameters have been shown to impede folding and generate incorrect structures. [27][28][29] Thus force field variations can affect sensitive biomolecular processes such as protein folding pathways.…”
Section: Introductionmentioning
confidence: 58%
“…Due to the complexity of the parameterization process, various force fields are not guaranteed to exhibit the same effect on biomolecular behavior. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] This has been seen previously when modifica-tions to torsion angle parameters have been shown to impede folding and generate incorrect structures. [27][28][29] Thus force field variations can affect sensitive biomolecular processes such as protein folding pathways.…”
Section: Introductionmentioning
confidence: 58%
“…experimental data for Aβ [63,64]. Moreover, AMBER FF14SB is fully compatible with 97 LIPID14 force-field [59], which is expected to provide optimal accuracy for both lipids 98 and peptide in the simulations.…”
Section: Introductionmentioning
confidence: 96%
“…AMBER FF14SB force-field is an improved version of FF99SB [60] used in 93 our previous simulations [52, 61]. Although older CHARMM force-fields tend to provide 94 better results for Aβ peptide than old AMBER force-fields [62], new AMBER versions, 95 especially AMBER FF14SB and CHARMM36m provide good agreement with 96experimental data for Aβ [63,64]. Moreover, AMBER FF14SB is fully compatible with 97 LIPID14 force-field [59], which is expected to provide optimal accuracy for both lipids 98 and peptide in the simulations.…”
mentioning
confidence: 99%
“…One of the main conclusions was that GROMOS54A7 13 and OPLS-AA 14,15 overstabilize protein-protein interactions, leading to an overestimation of the aggregation speed and an inhibition of protein-aggregate dissociation. Thereafter, Derreumaux and coworkers investigated the protein aggregation behavior for the Aβ 16−22 dimer using 17 different FFs in combination with conventional MD simulations, 16 following up their previous work where they had employed replica exchange MD to study dimers and trimers of Aβ 16−22 . 17 They concluded that FFs from CHARMM with updated CMAP correction 18,19 such as CHARMM22*, 20 CHARMM36, 21 and CHARMM36m, 9 along with FFs based on AMBER99 22 with modified torsional parameters for the backbone and for the four amino acids Ile, Leu, Asp, and Asn like AMBER99SB-ILDN 23 and AMBER14SB 24 are best suited for studying amyloid aggregation.…”
Section: Introductionmentioning
confidence: 99%